2010
DOI: 10.1210/jc.2009-1393
|View full text |Cite
|
Sign up to set email alerts
|

Association ofKCNQ1Polymorphisms with the Gestational Diabetes Mellitus in Korean Women

Abstract: KCNQ1 polymorphisms shown to be associated with increased risk for T2DM in the recent GWA study might also represent genetic factors contributing to the development of GDM in Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
2
28
2
Order By: Relevance
“…While we were preparing this paper, two similar reports regarding KCNQ1 and GDM were published [25,26]. The report of Shin et al [25] used our allele frequency data of the control subjects that was previously published [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we were preparing this paper, two similar reports regarding KCNQ1 and GDM were published [25,26]. The report of Shin et al [25] used our allele frequency data of the control subjects that was previously published [1].…”
Section: Discussionmentioning
confidence: 99%
“…The report of Shin et al [25] used our allele frequency data of the control subjects that was previously published [1]. However, the GDM group of Shin et al [25] was an independent population and our GDM group represented slightly more severe cases as it was diagnosed in more strict criteria. The two SNPs (rs2237892 and rs2237895) which were tested in all three studies showed similar allele frequencies, the same direction of association, as well as similar p values.…”
Section: Discussionmentioning
confidence: 99%
“…The C allele of the rs2237892 was associated with GDM in two Korean studies (Kwak et al, 2010;Shin et al, 2010) but not in the Chinese study (Zhou et al, 2009). Instead, rs2237896 and rs2237895 were associated with GDM in a Chinese population (Zhou et al, 2009).…”
Section: Kcnq1mentioning
confidence: 77%
“…These genes have also been studied in women with GDM of various races, including Americans, Europeans, Mediterraneans, Asians, and Arabians. The number of women with GDM included in these studies ranged greatly from 25 (Low, Mohd Tohit, Chong, & Idris, 2010) to 930 (Shin et al, 2010). Sample size powered at least 80% was reported in only 6 of 24 studies (King, 2007;Lauenborg et al, 2009;Pappa et al, 2011;Shaat et al, 2005;Zhou et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation